Social System under the Pallavas: The Role and Influence of Brahmins in Pallavas Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Brahmins occupied a regarded place in the Pallavas society. They had been well versed in the Sastras and Vedas. The Pallavas rulers patronized the Brahmins and also granted them with brahmadeya land gifts. The kings performed a lot of sacrifices as Aswamedha, Agnistoma and Vajapeya. The services of the Brahmins were required in the functionality of ceremonies and sacrifices. During the Pallavas rule substantial amount of Brahmins moved from the Andhara country to Tamilnadu, Dr. C. Minakshi is of the impression that some Brahmins had been used as court poets and also prasasti writers. Additionally they served in the variyams in the villages. They had been given with lands which were developed by the people of various other communities. Some Brahmins had been used in temples as teachers Kasakkudi plates the rights and responsibilities of each caste.